Implementation of real-time hardware-in-the-loop systems on multiple platforms - Phyo, May Kyi (2016)
With the rapid depletion of fossil fuels, the renewable microgrid power system is gaining interest in power generation to fulfill the required electricity demand. This project provides how solar microgrid is implemented to perform both offline and real-time (RT) simulation. The solar microgrid power system model mainly consists of solar photovoltaic (PV) array circuit, maximum power point tracking (MPPT) circuit, power utility grid, power electronics converters and constant and variable loads. The loads can be supplied either by DC supply or AC utility grid. The solar microgrid power system is modelled in MATLAB/Simulink and examined offline simulation result. Upon successful offline simulation, the model is simulated with Opal-RT software and simulator in order to achieve actual simulation result. Small step size is used for better accuracy however it takes a longer time to complete simulation. Thus, the complete power system is decoupled into small subsystems and assigned with respective CPU cores for RT simulation. Different synchronized step sizes are used to examine the performance of the system.